a) \(\frac{x^2+2x+4}{4x^3-32}=\frac{x^2+2x+4}{4\left(x^3-8\right)}=\frac{x^2+2x+4}{4\left(x-2\right)\left(x^2+2x+4\right)}=\frac{1}{4\left(x-2\right)}.\)
b) \(\frac{10x-15}{4x^2-9}=\frac{5\left(2x-3\right)}{\left(2x\right)^2-3^2}=\frac{5\left(2x-3\right)}{\left(2x-3\right)\left(2x+3\right)}=\frac{5}{2x+3}.\)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
HAND!!!!
\(\frac{x^2+2x+4}{4x^3-32}=\frac{\left(x+2\right)^2}{4\left(x^3-8\right)}=\frac{\left(x+2\right)^2}{4\left(x-2\right)\left(x^2+2x+4\right)}=\frac{x+2}{4\left(x^2+2x+4\right)}.\)
\(\frac{10x-15}{4x^2-9}=\frac{5\left(2x-3\right)}{\left(2x\right)^2-3^2}=\frac{5\left(2x-3\right)}{\left(2x-3\right)\left(2x+3\right)}=\frac{5}{2x+3}\)
câu 1 sai ròi tớ tưởng hằng đẳng thức -.-'
lm theo bn trc ý nhé